Bridging the Gaps Between Human Rights and Climate Governance at the International and Regional Judicial Spheres - Luhandjula, Yasmine (Southern African Public Law)
Climate litigation underscores the critical role of judicial systems in addressing the legal complexities that emanate from global climate governance. The lead-up to and the aftermath of the Paris Agreement saw the emergence of climate litigation with claims encompassing a human rights dominance. Climate litigation serves as a critical tool that not only exposes the deficiencies within the existing international climate change regime, but also sheds light on the pressing human rights issues arising from the widespread effects of climate change. This article examines the value and effectiveness of climate litigation in enhancing the connection between climate change impacts and the protection of human rights. This article emphasises the role of the international and regional judicial bodies in orchestrating the gaps and overlaps in the human rights and climate change regimes.